The writing on the wall? John Ingram's verse and the dissemination of Catholic prison writing. Issue 1 (31st March 2016) - Shell, Alison
Abstract : The strong association between prison writing and writing on walls, whether by graffiti or carving, is as true of Tudor and Stuart England as of other times and places. Yet even if prison-writers associated themselves with the idea of writing on a wall, they need not have done so in reality. This article considers the topos in the writings and afterlife of the Catholic priest, poet and martyr John Ingram, and asks whether it is to be taken at face value. Ingram's verse, composed in Latin and mostly epigrammatic, survives in two contemporary manuscripts. The notion that the author carved his verses with a blunt knife on the walls of the Tower of London while awaiting death derives from a previous editorial interpretation of a prefatory sentence within the more authoritative manuscript of the two, traditionally held to be autograph. However, though several Tudor and Stuart inscriptions survive to this day on the walls of the Tower of London, no portions of Ingram's verse are among them, nor any inscriptions of similar length and complexity. Ingram might instead have written his verse down in the usual way, using wall-carving as a metaphor for the difficulty of writing verse when undergoing incarceration and torture. 1